THERAPEUTIC ALLIANCE AND RELAPSES OF SUBSTANCE USE - N. El Moussaoui; B. Sofiya; T. Aicha; F. El Omari (European Psychiatry, 2023)
Introduction Therapeutic alliance is the key to ensure adequate and sustainable care in psychiatry. The therapeutic alliance has been the subject of a great deal of psychotherapy research, and evidence from numerous empirical studies suggests that a strong patient-therapist relationship predicts favorable treatment outcomes and continues to be regarded as an important aspect of the therapeutic process Objectives The purpose of this studie is to evaluate how the development of therapeutic alliance dimensions was associated with srelapses prevention. Methods This is a prospective, observational, cross-sectional study, carried out in the department of addictology at Ar-razi hospital in Salé using a therapeutic alliance measurement scale, and evaluating relapses’ frequency and duration of abstinence. The therapeutic alliance (TA) score was measured using Working Alliance Inventory. Results The results call upon the concepts of anomie and attachment, which seem to play an important role in the follow-up and prevention of relapses, indicating the need for a global approach to care and the involvement of health and social professionals, where empathy must find its place. Conclusions Decades of psychotherapy research suggest that the strength of the relationship between patient and therapist is a common factor that is associated with treatment response. In the context of relapses specifically, most of the studies reviewed found evidence for a significant alliance-outcome relationship. Disclosure of Interest None Declared